ANALISIS PREFERENSI MASYARAKAT TERHADAP BUS RAPID TRANSIT (BRT) TRANS SEMARANG - Tutus Kenanthus Avica Putra; Akhmad Syakir Kurnia (Universitas Diponegoro, 2014)
ABSTRACTLike other major cities, Semarang as the capitol city of the Central Java Province has problems in transportation. The problems emerge as a consequence of an increase in people mobility. At the same time, the quality of public transportation in Semarang has been a crucial issue as its development does not progress equally with the increase in people mobility.Using ordinary least square and binary logistic regression, this paper aims to analyse the preferences of public transportation users to use the Trans Semarang Bus Rapid Transit (BRT). Several variables namely the level of income, the private motorbike or car owning, and the BRT performance indicators are expected to explain the preferences of BRT. The probability of the BRT users to switch from BRT to other means of transportation when price is increased is expected to be explained using binary logistic regression. The result shows that the major users of the BRT are low level income households. Within this circumstance, the OLS estimation shows that price is sensitive to the BRT user preferences. An increase in the BRT price will result in higher probability of the BRT users to switch from BRT to other means of transportation. The level of income and the BRT performance have positive impact on the BRT user preferences. Private motorbike ownership has a negative effect against the BRT user preferences which means that motorbike is a close substitution to the BRT. However as the major users of BRT are low income households, we can not show any evidences that car ownership does matter for the BRT users.